Penegakan Hukum Administrasi Dalam Sengketa Kepemilikan Rumah Toko - Matuankotta, Jacky Alko Lazarus; Nendissa, Renny Heronia; Holle, Erick Stenly (Jurnal Saniri, 2025)
Article 28D paragraph (1) of the 1945 Republic of Indonesia Constitution states that: "Everyone has the right to recognition, guarantees, protection and certainty of fair law and equal treatment before the law." However, the reality in the field often does not match the ideality of the law. The decision of the Ambon City Government not to extend building rights  the shophouse in Ambon Plaza was made without a clear reason, thus creating legal uncertainty. The problem to be discussed by the author is to analyze the forms of administrative law enforcement and the legal consequences of the government not enforcing administrative law in shophouse ownership disputes. This study uses the Normative Juridical method, with an approach to statutory regulations, and a conceptual approach.. The results of the study indicate that the forms of administrative law enforcement that can be applied in shophouse ownership disputes consist of two main categories, namely through administrative instruments and administrative sanctions